An Early Iron Age palisaded enclosure in a multi-phase setting: excavations at Bleakmoor Hill. Issue 1 (2nd January 2022) - Hunter, Philippa; Waddington, Clive; Grzybowska, Milena; Parker, Luke; Hamilton, Derek
ABSTRACT: The dating of palisaded enclosures in Britain remains poorly understood with few sites having been directly dated by scientific means using suitable, reliable samples. Excavations to support a possible planning application for an extension at Harden Quarry, Northumberland, provided the impetus to investigate a Scheduled palisaded enclosure on the edge of the Cheviot Hills, where one of the largest concentrations of these monument types is known. Excavation was also undertaken on adjacent features including a ring cairn, clearance cairn, and land allotment boundary. The palisaded enclosure contained a multiphase settlement within it, but the palisaded phase of the site appeared to be single phase and was securely radiocarbon dated to the late sixth – fifth century cal. BC. It is thought most likely that the linear boundary feature relates to a field system connected to the use of the palisaded settlement. Evidence for Mesolithic activity on the hilltop was attested by chipped flints and radiocarbon dates from a later feature. The clearance cairn likely dates to the Beaker period whilst cremations from the ring cairn were dated to the Early Bronze Age. Later cord rigg agriculture could be seen to overlie the ring cairn, palisaded enclosure and linear boundary.